Transplantation of an adipose stem cell cluster in a spinal cord injury - Oh, Jin Soo; Park, In Su; Kim, Keung Nyun; Yoon, Do Heum; Kim, Sang-Heon; Ha, Yoon (LIPPINCOTT WILLIAMS & WILKINS, 2012)
We investigated whether transplantation of a three-dimensional cell mass of adipose-derived stem cells (3DCM-ASCs) improved hind limb functional recovery by the stimulation of angiogenesis and neurogenesis in a spinal cord injury. In in-vitro experiments, we confirmed that 3DCM-ASCs differentiated into CD31-positive endothelial cells. To evaluate the therapeutic effect of 3DCM-ASCs in vivo, PBS, human adipose tissue-derived stem cells, and 3DCM-ASCs were transplanted into a spinal cord injury model. The 3DCM-ASCs transplanted into the injured spinal cord differentiated into CD31-positive endothelial cells and remained differentiated. Transplantation of 3DCM-ASCs into the injured spinal cord significantly elevated the density of vascular formations through angiogenic factors released by the 3DCM-ASCs at the lesion site, and enhanced axonal outgrowth at the lesion site. Consistent with these results, the transplantation of 3DCM-ASCs significantly improved functional recovery compared with both ASC transplantation and PBS treatment. These findings suggest that transplantation of 3DCM-ASCs may be an effective stem cell therapy for the treatment of spinal cord injuries and neural ischemia. NeuroReport 23: 277-282 (C) 2012 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: BONE-MARROW; ANGIOGENESIS; TISSUE; VIVO